2005
DOI: 10.1002/glia.20277
|View full text |Cite
|
Sign up to set email alerts
|

Functional demonstration of surface carbonic anhydrase IV activity on rat astrocytes

Abstract: Buffering of the brain extracellular fluid is catalyzed by carbonic anhydrase (CA) activity. Whereas the extracellular isoform CA XIV has been localized exclusively to neurons in the brain, and to glial cells in the retina, there has been uncertainty regarding the form or forms of CA on the surface of brain astrocytes. We addressed this issue using physiological methods on cultured and acutely dissociated rat astrocytes. Prior work showed that the intracellular lactate-induced acidification (LIA) of astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 45 publications
2
31
0
1
Order By: Relevance
“…Both studies confirmed an earlier study showing that no CA IV was detected in retina (27). An example of the other extreme was suggested by the observation that CA IV is the dominant, if not the only, CA expressed on the surface of both isolated and cultured cortical astrocytes (24).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Both studies confirmed an earlier study showing that no CA IV was detected in retina (27). An example of the other extreme was suggested by the observation that CA IV is the dominant, if not the only, CA expressed on the surface of both isolated and cultured cortical astrocytes (24).…”
Section: Discussionsupporting
confidence: 87%
“…The only CA known at that time that would be expected to be removed by this treatment was the glycosylphosphatidylinositol-anchored CA IV. In addition, another study recently demonstrated that nearly all of the extracellular CA on the surface of rat astrocytes was attributable to CA IV (24). On the other hand, immunocytochemical studies showed that CA XIV was present on some neurons and axons in brain tissue (14), leading Parkkila et al (14) to suggest that CA XIV was also important.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, in mouse hippocampal slice preparations, CA IV has a greater effect on regulation of extracellular pH than CA XIV (12). CA IV is localized to neuronal and axonal membranes in the hippocampus (31) and has been found to be the only extracellular CA found on the surface of isolated rat astrocytes from neonatal brain (32). In contrast, in Müller glial cells in retina from both human and mouse, CA IV is not detectable and CA XIV expression is very high (8)(9)(10).…”
Section: Discussionmentioning
confidence: 98%
“…As reported before, uptake and/or release of lactate in astrocytes are mediated via MCT1 and MCT4 (50 -52). Furthermore, astrocytes play a pivotal role in acid/base regulation in the brain, and thus highly express intracellular CAII and extracellular CAIV (31,53,54). Therefore, MCT1, MCT4, CAII, and CAIV might cooperate in astrocytes to ensure both rapid shuttling of lactate to neurons and efficient uptake of lactate from the extracellular space under different physiological conditions.…”
Section: Discussionmentioning
confidence: 99%